الفعل الحيوي لبعض أنواع الفطر Trichoderma إزاء الفطرين الممرضين oxysporum Fusarium و solani .F - علي, نوال; حسن, محمود; شعبان, سومر (Latakia University Journal -Biological Sciences Series, 2019)
تم دراسة تأثير كل من الفطرين Trichoderma harzianum و T.viride المعزولين من تربة محلية والمنتج الحيوي التجاري Biocont الحاوي على الفطر T.harzianum في تثبيط نمو الفطرين Fusarium oxysporum وsolani F. . أظهرت أنواع التريكوديرما المدروسة كفاءة تنافسية متباينة تجاه الفطرين الممرضين Fusarium oxysporum وsolani F.، إذ تفوّق الفطر T.viride على باقي الأنواع في تثبيط F. oxysporum بنسبة وصلت إلى73.6%. كما أبدت أنواع Trichoderma قدرة على إفراز مواد متطايرة تسببت في تثبيط مستعمرة الفطر Fusarium، مقارنة بالشاهد. وتباينت نسبة التثبيط تبعا لنوع التريكوديرما وعمر المستعمرة. بلغت كفاءة المواد المتطايرة من الفطر T.viride في تثبيط نمو F. oxysporum و solani F. نسبة 49 %و40% على التوالي. و بلغت كفاءة المواد المتطايرة من الفطر T.harzianum في تثبيط نمو F. oxysporum وsolani F. مقدار 44 %و35% على التوالي. وعند اختبار تأثير المواد غير المتطايرة التي يفرزها T.harzianum أظهرت نسبة تثبيط لنمو الفطر F. oxysporum وصلت إلى 54%. تبين تفوق العزلة المحلية T.harzianum على المستحضر التجاري في تثبيط نموF .oxysporum و solani F. The antagonistic effect of Trichoderma harzianum , and T .viride fungi that have been isolated from local soils and a biological commercial product(Biocont which includes T.harzianum) on the growth of Fusarium oxysporumi and F. solani has been studied. The competitive efficiency of the studied Trichoderma species inhibiting the two pathogenic fungi was quite varied. The T. viride for instance outmatched all other remaining species at a rate of 73.6%. Compared to the control, the Fusarium colony was actively inhibited due to the ability of secretion of volatile materials by some species of Trichoderma, and such rate of inhibition experienced clear variances due to the effect of some characteristics of Trichoderma species and age of colony. The efficiency of those volatile materials from T. viride fungi in inhibiting the growth of Fusarium oxysporum and F.solani was 49% and 40% respectively, whereas the Trichoderma harzianum volatile materials were 44% efficient in inhibiting the growth of Fusarium oxysporum and only 35% efficient in inhibiting the growth of F.solani. The results of this study have shown that non-volatile materials secreted by Trichoderma harzianum possess the inhibition rate of growth of Fusarium oxysporum by 54%, and made clear that the effect of using Trichoderma harzianum was much better than using Biocont.